2018
DOI: 10.5194/npg-25-537-2018
|View full text |Cite
|
Sign up to set email alerts
|

OSSE for a sustainable marine observing network in the Sea of Marmara

Abstract: Abstract. An observing system simulation experiment (OSSE) is presented in the Sea of Marmara. A highresolution ocean circulation model (FESOM) and an ensemble data assimilation tool (DART) are coupled. The OSSE methodology is used to assess the possible impact of a FerryBox network in the eastern Sea of Marmara. A reference experiment without assimilation is performed. Then, synthetic temperature and salinity observations are assimilated along the track of the ferries in the second experiment. The results sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
4
9
0
1
Order By: Relevance
“…They reproduced the S-shaped jet current traversing the basin under the isolated conditions of a net barotropic current, which with appropriate parameterisation successfully preserved the sharp interface between the upper and lower layers when the model steady state was reached after 18 years of simulation. The S-shaped upper layer circulation of the Sea of Marmara predicted by Demyshev et al (2012) appears similar to what Beşiktepe et al (1994) found in summer, when wind forcing is at its minimum or at least close to being in a steady state. An anticyclonic pattern has generally been identified in the central Sea of Marmara, like the cases reported by Beşiktepe et al (1994).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…They reproduced the S-shaped jet current traversing the basin under the isolated conditions of a net barotropic current, which with appropriate parameterisation successfully preserved the sharp interface between the upper and lower layers when the model steady state was reached after 18 years of simulation. The S-shaped upper layer circulation of the Sea of Marmara predicted by Demyshev et al (2012) appears similar to what Beşiktepe et al (1994) found in summer, when wind forcing is at its minimum or at least close to being in a steady state. An anticyclonic pattern has generally been identified in the central Sea of Marmara, like the cases reported by Beşiktepe et al (1994).…”
Section: Introductionsupporting
confidence: 75%
“…Climatological means of water and tracer fluxes through the TSS were initially estimated from long-term observations of seawater properties at junctions of the straits and on surface water fluxes (Ünlüata et al, 1990;Beşiktepe et al, 1994;Tugrul et al, 2002;Maderich et al, 2015), followed later by ship-borne and moored acoustic Doppler current profiler (ADCP) measurements at the straits (Özsoy et al, 1988, 1998Altıok et al, 2012;Jarosz et al, 2011bJarosz et al, , a, 2012Jarosz et al, , 2013. Updated reviews of TSS fluxes based on combined data have been provided by Schroeder et al (2012), Özsoy and Altıok (2016), Sannino et al (2017) and Jordá et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the two-way travel time measurement, the acoustic signals travel in forward and backward direction and directional effects imposed by water fluxes cancel out. This is only possible since the temporal changes of water currents are clearly slower than our two-way travel times, which are mostly below 3 s. Overall little is known on the accurate water parameters on the seafloor of the Sea of Marmara because most stations measuring oceanic parameters are located at shallow water depths 47 . The temperature and pressure are measured at the active transponder during the TWT measurement; the velocity along the acoustic path is approximated by the harmonic mean of the sound velocities of water at the stations (i.e.…”
Section: Methodsmentioning
confidence: 90%
“…OSSE have been conducted in the last decade in the regional ocean (e.g., Halliwell et al, 2014, Halliwell et al, 2015Aydogdu et al, 2018). One particular challenge is to develop a rigorous OSSE approach for the interaction of open-sea and coastal scales (with particular focus on coastal scales where observations are sparser and scales shorter) adopting multi-scale models as Nature Runs to back up synthetic observations (e.g., Oke et al, 2015;Fujii et al, 2019).…”
Section: Using Models To Design and Optimize Coastal Observing Systemsmentioning
confidence: 99%
“…Moreover, long-term repeated glider missions along endurance lines were shown to provide a new view of the ocean variability in narrow channels (Heslop et al, 2012) and in the transition zone between coastal and the open ocean (Rudnick et al, 2017). The HF sampling of surface coastal waters by FerryBox systems also delivers observations that improve assimilated model simulations (Korres et al, 2014;Stanev et al, 2016;Aydogdu et al, 2018). Particularly, in waters where the ocean dynamics are tidally driven, the assimilating FerryBox will be more efficient than slower glider platforms (Charria et al, 2016).…”
Section: Using Models To Design and Optimize Coastal Observing Systemsmentioning
confidence: 99%